Use of acenocoumarol in cardioembolic stroke: an evidence-based review - Meenakshisundaram, S.; Kaul, Subhash; Mudgerikar, Sucheta; Sharma, U. P. (International Journal of Advances in Medicine, 2024)
Stroke is the leading cause of long-term disability and the second most common cause of death worldwide. Nearly two-thirds of all strokes represent cerebral ischemia, of which about 15%-30% are of cardioembolic origin. Atrial fibrillation accounts for about 60% of all cardioembolic strokes. Current clinical evidence suggests that oral anticoagulant therapy can prevent around 70% of strokes in patients with atrial fibrillation. Oral anticoagulation therapy is preferred over antiplatelet therapy in patients with cardioembolic stroke. Vitamin K antagonists (VKAs) and nonvitamin K antagonist oral anticoagulants (NOACs) are routinely prescribed oral anticoagulants in patients at risk of stroke; however, there are specific indications where VKA use surpasses NOAC use or there are conditions where NOACs are contraindicated. A group of experts revisited the role of oral anticoagulants in the management of cardioembolic stroke in India with emphasis on VKA, specifically acenocoumarol. This article discusses various aspects of anticoagulation therapy, including the timing of initiation and patient monitoring, in patients with cardioembolic stroke with reference to current clinical evidence and expert opinion based on Indian clinical experience.